2015
DOI: 10.1186/s12889-016-2784-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of tetanus, pneumococcal and influenza vaccination in the elderly: a representative cross-sectional study on knowledge, attitude and practice (KAP)

Abstract: BackgroundSeverity and incidence of vaccine-preventable infections with influenza viruses, s. pneumoniae and c. tetani increase with age. Furthermore, vaccine coverage in the elderly is often insufficient. The aim of this study is to identify socio-economic and knowledge-, attitude- and practice- (KAP)-related determinants of vaccination against influenza, pneumococcal disease and tetanus in the older German population.MethodsWe analysed data from a German nationally representative questionnaire-based KAP-surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 26 publications
7
71
1
4
Order By: Relevance
“…As for vaccination, only 17% of the participants were aware that it reduces the risk of sepsis [9]. This latter finding corroborates those of previous studies which reported that the perception of the severity of pneumonia was associated with receiving vaccination, especially amongst elderly persons [29][30][31].…”
Section: Cap Affects Everyone: Why Do We Not Recognize the Threat?supporting
confidence: 86%
“…As for vaccination, only 17% of the participants were aware that it reduces the risk of sepsis [9]. This latter finding corroborates those of previous studies which reported that the perception of the severity of pneumonia was associated with receiving vaccination, especially amongst elderly persons [29][30][31].…”
Section: Cap Affects Everyone: Why Do We Not Recognize the Threat?supporting
confidence: 86%
“…Elderly adults who scored more highly on knowledge questions were more likely to have been vaccinated 40,51,57,58 while unvaccinated subjects knew little about influenza symptoms 38 and the side-effects of the vaccine. 39 Elderly people would have more positive beliefs towards vaccination and be more likely to accept vaccination if they received knowledge/ information from healthcare professionals.…”
Section: Knowledge/information and Its Sourcesmentioning
confidence: 99%
“…Three studies 50,51,58 that used vaccination intention as an independent variable and explored its impact on vaccination behaviour suggested that those who intended to be vaccinated were more likely to have ever undergone vaccination. Five studies 39,46,47,50,57 employed vaccination intention and vaccination behaviour as dependent variables, and two studies 44,54 adopted vaccination intention as the only outcome variable.…”
Section: Behavioural Intentionmentioning
confidence: 99%
“…The three levels of understanding obtained allow for better design of strategies or programs taking into account the community's perceptions and needs. 23,24,25,26 We hypothesized that knowledge of the disease and risk perception, together with confidence in health system would be associated with willingness to participate in a vaccine trial.…”
Section: Introductionmentioning
confidence: 99%